Commodity risk assessment of Prunus domestica plants from Ukraine. (22nd June 2022) - ,; Bragard, Claude; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Baptista, Paula; Gonthier, Paolo; Jacques, Marie‐Agnès; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; et al.
Abstract: The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as 'High risk plants, plant products and other objects'. This Scientific Opinion covers plant health risks posed by plants of Prunus domestica grafted on Prunus cerasifera imported from Ukraine, taking into account the available scientific information, including the technical information provided by Ukraine. All pests associated with the commodity were evaluated against specific criteria for their relevance for this opinion. One quarantine pest ( Lopholeucaspis japonica ), two protected zone quarantine pests ( Erwinia amylovora and Xanthomonas arboricola pv. pruni ) and one non‐regulated pest ( Eotetranychus prunicola ) that fulfilled all relevant criteria were selected for further evaluation. For these four pests, the risk mitigation measures proposed in the technical dossier from Ukraine were evaluated taking into account the possible limiting factors. For the selected pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The degree of pest freedom varies among the pests evaluated, with Xanthomonas arboricola pv. pruni being the pest most frequently expected on the imported plants. The Expert Knowledge Elicitation indicated with 95% certainty that between 9, 870 and 10, 000 bundles (consisting of 10 plants each) per 10, 000 would be free from Xanthomonas arboricola pv. pruni .